PEMBERIAN KOMPOS BRANGKASAN TANAMAN JAGUNG DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays Saccharata) - Zefanya Pandalahat Sidabutar; Ardian Ardian; Husna Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aim to know the interaction and the effect of application of compost brangkasan corn and NPK fertilizer and get the dose of fertilizer of the growth and production of sweet corn. This research has been conducted from june until september 2018. This research has been conducted on the experimental field using a complete design random (CDR) with 2 factor. The first factor is the contration of compost that consist of level: 2,5 t.ha-1, 5 t.ha-1, and 7,5 t.ha-1. The second factor is the dose of NPK fertilizer that consist of level: 50 kg.ha-1, 100 kg.ha-1 and 150 kg.ha-1. The observed parameters of plant height, stem diameter, number of leaves, time of male flower, time of female flower, cob length, cob diameter, cobs are weightless, cobs not weighted and the number of seeds per line. The result showed that the interaction of application compost brangkasan corn and NPK fertilizer have non significant effect. Application NPK fertilizer have non significant effect. Application compost brangkasan corn had significant effect on all parameters amount plant heigh, time of male flower, time of female flower, cobs are weightless, cobs not weighted and the number of seeds per line. Application compost brangkasan corn 5 t.ha-1 and NPK fertilizer 150 kg.ha-1 show on average the highest of any parameter observation give growth and production of good.Keywords : corn, compost brangkasan, NPK.